2023
DOI: 10.1523/eneuro.0288-23.2023
|View full text |Cite
|
Sign up to set email alerts
|

Pupil Size Sensitivity to Listening Demand Depends on Motivational State

Frauke Kraus,
Jonas Obleser,
Björn Herrmann

Abstract: Motivation plays a role when a listener needs to understand speech under acoustically demanding conditions. Previous work has demonstrated pupil-linked arousal being sensitive to both listening demands and motivational state during listening. It is less clear how motivational state affects the temporal evolution of the pupil size and its relation to subsequent behavior. We used an auditory gap detection task (N = 33) to study the joint impact of listening demand and motivational state on the pupil size respons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 81 publications
2
14
0
Order By: Relevance
“…Moreover, pupil size dynamics during high listening demands are now known to be modulated by an individual's motivational state (Bijleveld et al, 2009;Zhang et al, 2019); recently confirmed by us using highly-controlled noise stimuli (Kraus et al, 2023a) as in the present study's experimental paradigm. This motivation-driven additional cognitive investment indexed by pupil dilation predicted better behavioral outcomes (Kraus et al, 2023a).…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Moreover, pupil size dynamics during high listening demands are now known to be modulated by an individual's motivational state (Bijleveld et al, 2009;Zhang et al, 2019); recently confirmed by us using highly-controlled noise stimuli (Kraus et al, 2023a) as in the present study's experimental paradigm. This motivation-driven additional cognitive investment indexed by pupil dilation predicted better behavioral outcomes (Kraus et al, 2023a).…”
Section: Introductionsupporting
confidence: 76%
“…Similar to our previous approach (Kraus et al, 2023a), we investigated whether a smaller pupil size is associated with an increased probability that a participant misses a gap or responds slower to the gap.…”
Section: Pupil Size Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, pupil size can vary due to factors unrelated to task demands, such as changes in light (Knapen et al, 2016;Suzuki et al, 2019;Thurman et al, 2021) or in the angle of the eye relative to the eye-tracking camera (Brisson et al, 2013;Hayes and Petrov, 2016;Fink et al, 2021). To address the latter, individuals typically maintain fixation on a point on a computer monitor (Zekveld et al, 2018;Winn and Teece, 2021;Kraus et al, 2023a), but restriction of gaze can reduce memory and mental imagery (Johansson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, pupil size can vary due to factors unrelated to task demands, such as changes in light (Knapen et al, 2016; Suzuki, Minami, Laeng, & Nakauchi, 2019; Thurman et al, 2021) or in the angle of the eye relative to the eye-tracking camera (Brisson et al, 2013; Fink et al, 2023; Hayes & Petrov, 2016). To address the latter, individuals typically maintain fixation on a point on a computer monitor (Kraus, Obleser, & Herrmann, 2023; Matthew B. Winn & Teece, 2021; Adriana A.…”
Section: Introductionmentioning
confidence: 99%